2009
DOI: 10.1007/s11104-009-0239-z
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizae improves low temperature stress in maize via alterations in host water status and photosynthesis

Abstract: The effect of arbuscular mycorrhizal (AM) fungus, Glomus etunicatum, on growth, water status, chlorophyll concentration and photosynthesis in maize (Zea mays L.) plants was investigated in pot culture under low temperature stress. The maize plants were placed in a sand and soil mixture at 25°C for 7 weeks, and then subjected to 5°C, 15°C and 25°C for 1 week. Low temperature stress decreased AM root colonization. AM symbiosis stimulated plant growth and had higher root dry weight at all temperature treatments. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
92
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(107 citation statements)
references
References 38 publications
10
92
0
5
Order By: Relevance
“…Although root hairs contributed to the improvement of gas exchange, the influence of root hairs was not as significant as that of the AM fungus. Gas exchange has been reported to correlate with uptake and transport of water and nutrients (Zhu et al 2010). It can be speculated from the present study that, based on shoot P concentration, P uptake by both root hairs and R. intraradices was conducive to an increase in gas exchange.…”
Section: Discussionmentioning
confidence: 49%
“…Although root hairs contributed to the improvement of gas exchange, the influence of root hairs was not as significant as that of the AM fungus. Gas exchange has been reported to correlate with uptake and transport of water and nutrients (Zhu et al 2010). It can be speculated from the present study that, based on shoot P concentration, P uptake by both root hairs and R. intraradices was conducive to an increase in gas exchange.…”
Section: Discussionmentioning
confidence: 49%
“…Mycorrhizing decrease role of salt in chlorophyll synthesis (Giri and Mukerji, 2004). In Glomus etunicatum inoculated maize plant, increase in photosynthesis speed, transpiration and chlorophyll a, b density was reported under cold stress (Zhu et al, 2010). Also in Jatropha curcas mycorrhizal plants higher chlorophyll were reported than non-mycorrhizal plants under salt stress conditions (Ashwani et al, 2010).…”
Section: Chlorophyll Contentmentioning
confidence: 99%
“…When maize plants were subject to low temperature stress, AM symbiosis could enhance stressed tolerance of maize plants via alterations in host water status, carbohydrate, protein, antioxidant enzyme activities (Zhu et al 2009(Zhu et al , 2010. However, other studies observed that the mycorrhizal benefit for the host plant (e.g.…”
mentioning
confidence: 99%